Iowa RBA, November 2, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for November 2, 1998. Highlights include White-winged Scoter, Black Scoter, Eurasian Collared Dove, and California Gull. Includes notes for updates for November 4, and November 5. Epson - sheet feed/flatbed